Longitudinal Changes in Cardiac Structure and Function in Severe Obesity: 11‐Year Follow‐Up in the Utah Obesity Study. Issue 12 (16th June 2020) - Litwin, Sheldon E.; Adams, Ted D.; Davidson, Lance E.; McKinlay, Rodrick; Simper, Steven C.; Ranson, Lauren; Hunt, Steven C.
Abstract : Background: Progressive cardiac remodeling and worsening myocardial function over time have been proposed as potential mediators of heart failure in obesity. Methods and Results: We serially assessed cardiac structure and function in 254 subjects participating in a longitudinal study of obesity. Demographic, clinical, laboratory, and echocardiographic features were determined at baseline and 2‐, 6‐, and 11‐year follow‐up. We measured body mass index (BMI) exposure as the area under the curve of the BMI at each of the 4 visits. At enrollment, mean age of the subjects was 47 years, 79% were women, mean BMI was 44 kg/m 2, 26% had diabetes mellitus, 48% had hypertension, and 53% had hyperlipidemia. Between baseline and 11 years, BMI increased by 1.1 and 0.3 kg/m 2 in men and women, respectively. There were modest increases in left ventricular (LV) end‐diastolic volume, LV mass, and left atrial volume, and significant decreases in early/late mitral diastolic flow velocity ratio and E wave deceleration time. However, there were no significant changes in LV ejection fraction or ratio of early mitral diastolic flow velocity/early mitral annular velocity, whereas right ventricular fractional area change increased. Significant predictors of the change in LV mass were male sex, baseline BMI, BMI area under the curve, and change in LV stroke volume, but not smoking, hypertension, or diabetes mellitus. Conclusions: In long‐standing, persistent severe obesity, there was evidence of cardiac remodeling over a period of 11 years, but no clear worsening of systolic or diastolic function. Measures of remodeling were most strongly related to BMI. The observed changes might predispose to heart failure with preserved ejection fraction, but are not classic for an evolving dilated cardiomyopathy.